Fatigue Assessment Using FACIT-F Scale In Axial Spondyloarthropathy, Rheumatoid Arthritis And Systemic Lupus Erythematosus Patients Presenting To A Tertiary Care Hospital - Shafqat, Saira; Khaliq, Taqdees; Shah, Sarah Azam; Abbasi, Qurat ul Ain (Journal of Rawalpindi Medical College, 2025)
Objective: To measure fatigue in patients with axial spondyloarthropathy, Rheumatoid Arthritis and Systemic lupus erythematosus and find its correlation with the disease activity measures. Methods: This Cross-sectional, descriptive study was carried out in the Rheumatology Unit of the Federal Government Polyclinic Hospital from October 2024 to April 2025. This study included a total of 135 patients, with 45 patients meeting the ASAS criteria for spondyloarthropathy. Disease activity in ankylosing spondylitis (AS) patients was assessed using the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI). The Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-F) scale was used to evaluate fatigue in all patients. Results: A total of 90 (66.6%) female patients and 45 (33.3%) male patients were included. Severe fatigue with a FACIT-F score of <30 was found in 81 (60%) of all included patients. Among the spondylarthritis group, the mean FACIT fatigue score was found to be 26 ±9.37, for RA it was 26.60 ±11.23, while that in the SLE cohort was found to be 28.86 ±12.40. Demographic profiles suggest that fatigue was most common in AS patients (68.8%), followed by RA (62.2%) and then by SLE (48.89%). The mean value of the FACIT score varied with the activity of the disease in all three diseases studied in this cohort. An independent sample t-test was used to compare the mean difference in the FACIT score among the ankylosing spondylitis patients, while ANOVA was used to find the difference in means among the RA and SLE patients, respectively. Conclusion: Patients with active disease and higher disease scores had a lower FACIT-F score, suggesting more fatigue, thus correlating with the disease activity. Key Words: Fatigue, Ankylosing spondylitis, Systemic lupus erythematosus, Rheumatoid arthritis.